Biochar Addition Altered Bacterial Community and Improved Photosynthetic Rate of Seagrass: A Mesocosm Study of Seagrass Thalassia hemprichii - Zhang, Jian; Ling, Juan; Zhou, Weiguo; Zhang, Wenqian; Yang, Fangfang; Wei, Zhangliang; Yang, Qingsong; Zhang, Ying; Dong, Junde (Frontiers in Microbiology, 2021)
Seagrass meadows, as typical “blue carbon” ecosystems, play critical ecological roles in the marine ecosystem and decline every year. The application of biochar in soil has been proposed as a potential soil amendment to improve soil quality and mitigate global climate change. The effects of biochar on soil bacterial activities are integrally linked to the potential of biochar in achieving these benefits. However, biochar has been rarely applied in marine ecosystems. Whether the application of biochar could work on the seagrass ecosystem remained unknown. In this study, we investigated the responses of sediment and rhizosphere bacterial communities of seagrass Thalassia hemprichii to the biochar addition derived from maize at ratios of 5 % by dry weight in the soil during a one-month incubation. Results indicated that the biochar addition significantly changed the sedimental environment with increasing pH, total phosphorus, and total kalium while total nitrogen decreased. Biochar addition significantly altered both the rhizosphere and sediment bacterial community compositions. The significant changes in rhizosphere bacterial community composition occurred after 30 days of incubation, while the significant variations in sediment bacterial community composition, distinctly delayed than in sediment occurred on the 14th day. Biochar application improved nitrification and denitrification, which may accelerate nitrogen cycling. As a stabilizer to communities, biochar addition decreased the importance of deterministic selection in sediment and changed the bacterial co-occurrence pattern. The biochar addition may promote seagrass photosynthesis and growth by altering the bacterial community compositions and improving nutrient circulation in the seagrass ecosystem, contributing to the seagrass health improvement. This study provided a theoretical basis for applying biochar to the seagrass ecosystem and shed light on the feasible application of biochar in the marine ecosystem.